2018
DOI: 10.1002/jsfa.9229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hot air treatment in combination with Pichia guilliermondii on postharvest preservation of peach fruit

Abstract: The combined treatment could control fungal diseases, besides delay the decline of quality and antioxidant parameters, so as to achieve the purpose of fresh keeping for harvested peach fruit. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 59 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…The SSC in the CF‐3 + HT group was higher than that of the other treatment groups in peach and litchi fruit (Figure 2B and 7B). Previous studies reported that the heat treatment combined with P. guilliermondii showed a significantly higher SSC than the control postharvest in apples (Zhao & Yin, ) and peaches (Zhao et al., ).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The SSC in the CF‐3 + HT group was higher than that of the other treatment groups in peach and litchi fruit (Figure 2B and 7B). Previous studies reported that the heat treatment combined with P. guilliermondii showed a significantly higher SSC than the control postharvest in apples (Zhao & Yin, ) and peaches (Zhao et al., ).…”
Section: Resultsmentioning
confidence: 89%
“…In fruit, it is common for weight loss to increase with increasing storage time. Proper heat treatment decreases the respiration rate and ethylene production, thereby maintaining the integrity of the membrane structure (Zhao et al., ), and interrupts the evapotranspiration pathway by covering the microfractures of the peach skin and litchi rind, resulting in a more even distribution of cuticular fruit waxes (Garcia et al., ). CF‐3 + HT treatment can effectively reduce the weight loss of peach and litchi fruit during storage (Figure 2A and 7A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations